A mcr-1-Carrying Conjugative IncX4 Plasmid in Colistin-Resistant Escherichia coli ST278 Strain Isolated From Dairy Cow Feces in Shanghai, China - Bai, Fengjia; Li, Xiaobin; Niu, Ben; Zhang, Zhaohuan; Malakar, Pradeep K.; Liu, Haiquan; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2018)
Acquired colistin resistance gene mcr-1 is widely spread in Enterobacteriaceae, including Escherichia coli with more than two-hundred different sequence types. However, knowledge about the genetic context of mcr-1 and characteristics of mcr-1- harboring E. coli is still limited. In this study, an E. coli strain EC11 with resistance to colistin was isolated in 2016 from the dairy cow feces in Shanghai, China. The strain EC11 was determined to be ST278, which displayed the susceptibility to 22 frequently used antibiotics, but the resistance to colistin, polymyxin B, and trimethoprim-sulfamethoxazole. Whole genome sequencing revealed that EC11 carries a 31-kb resistance plasmid pEC11b of IncX4 group. The mcr-1 gene was inserted into a 2.6-kb mcr-1-pap2 cassette of pEC11b. The putative conjugal transfer components, including oriT-like region, relaxase, type IV coupling protein, and type IV secretion system, were also detected in pEC11b. This pEC11b was subsequently found to be transferable to E. coli C600 with the transconjugation frequency of 4.6 × 10-5 cells per recipient. To our knowledge, this is the first report on a mcr-1-carrying E. coli strain isolated from dairy cow feces in Shanghai, which might reinforce our understanding of the antibiotic resistance in the food chain. Moreover, there is an urgent need to take the proactive strategies for monitoring the use of colistin and surveying the diffusion of mcr-1 gene in livestock farming.